Análisis doctrinario y jurídico del apremio personal para determinar su eficacia en el desarrollo integral de los derechos de los niños, niñas y adolescentes - Cañar Sivisapa, Bryan Fernando (2023)
The present Curricular Integration Work titled: "Doctrinal and legal analysis of personal pressure to determine its effectiveness in the integral development of the rights of children and adolescents", is considered as an object of study in view of the fact that it is very frequent to observe that there is still controversy about the effectiveness of the personal urgency ticket in terms of food to guarantee the integral development of children and adolescents and protect the best interests of the child since many people consider that this measure is not effective to protect the constitutional principle of the best interests of the child, but on the contrary it generates an increase in the number of unfulfilled pensions. The right to food is a connatural obligation of parents for their children and when this obligation is breached, a violation of rights is generated, for which the intervention of the State is necessary to guarantee this right through the application of necessary measures to guarantee the welfare of the minor. From the study carried out, it is evident that the personal enforcement notices in terms of food are not effective in guaranteeing the rights of children and adolescents, since in most cases the amount owed is not canceled due to non-compliance with alimony payments. In addition, it was also possible to determine that the procedure for the issuance of the pressure ticket is very lengthy and many times the requested measure is not obtained since only payment commitments are reached that do not present any guarantee and are not fulfilled. For the development of this investigative work, materials and methods were applied, as well as surveys and interviews with legal professionals, whose results served as a foundation to strengthen the proposed study topic and to develop clear and coherent criteria.